Corneal and Corneoscleral Injury in Combat Ocular Trauma from Operations Iraqi Freedom and Enduring Freedom. (1st March 2017) - Vlasov, Anton; Ryan, Denise S.; Ludlow, Spencer; Coggin, Andrew; Weichel, Eric D.; Stutzman, Richard D.; Bower, Kraig S.; Colyer, Marcus H.
ABSTRACT: Objectives: To examine the incidence and the etiology of corneal and corneoscleral injuries in the setting of combat ocular trauma, and to determine what effect these injuries have on overall visual impairment from combat ocular trauma. Methods: Retrospective, noncomparative, interventional case series, analyzing U.S. service members who were evacuated to the former Walter Reed Army Medical Center (WRAMC). Primary outcome measures were types of corneal injuries, length of follow-up at WRAMC, globe survival, and anatomical causes of blindness. Secondary outcome measures included surgical procedures performed, use of eye protection, source of injury, and visual outcomes. Results: Between 2001 and 2011, there were 184 eyes of 134 patients with corneal or corneoscleral injuries. The average age was 26 years (range, 18–50); 99.3% were male, 31.9% had documented use of eye protection. The average follow-up was 428.2 days (3–2, 421). There were 98 right-eye and 86 left-eye injuries. There were 169 open-globe and 15 closed-globe injuries with corneal lacerations occurring in 73 eyes with injuries to Zone I. Most injuries were attributable to an intraocular foreign body (IOFB; 48%), followed by penetrating (19.6%) and perforating (16.3%) injuries. The most common presenting visual acuity was hand motion/light perception (45.7%), yet, at the end of the study, visual acuity improved to 20/40 or better (40.8%). The majority of injuries in eyes with visual acuity worse than 20/200 involved the cornea and retina (58%). Injuries solely to the cornea accounted for only 19% of all injuries sustained. Conclusions: Ocular injuries in military combat have led to significant damage to ocular structures with a wide range of visual outcomes. The authors describe corneal and corneoscleral injuries in combat ocular trauma by classifying injuries by the anatomical site involved and identifying the main source of decreased visual acuity. In combat ocular trauma, corneal or corneoscleral injuries are not the sole etiology for poor vision. A cohesive approach among multiple ophthalmic subspecialties is needed when treating combat ocular trauma.